IMPROVEMENT OF METHODS OF DIAGNOSTICS AND TREATMENT OF CHLAMYDIAL PNEUMONIA IN CHILDREN (International Journal of Scientific Pediatrics, 2025)
Introduction. Introduction. Pneumonia is dangerous not only for children but also for adults. First of all, it is connected with the risk of severe complications. One of the most common diseases in children is pneumonia, which occupies a worthy place in morbidity and mortality. The aim of this work was: to study the effectiveness of combined use of antibacterial and antiviral drugs for chlamydial pneumonia in children. Materials and methods of the study: 42 patients aged 3 to 14 years were observed, who were divided into 2 groups. 21 patients were prescribed complex therapy, including the antibiotic josamycin and the antiviral drug Viferon suppositories in age-appropriate doses for 7 days. For the diagnosis of atypical pneumonia for the purpose of correct study of the pathogen, laboratory methods are used: bacteriological culture of sputum, nasopharyngeal smears on a nutrient medium; ELISA, PCR. In the treatment of chlamydial pneumonia, macrolides are used as the main course for at least 7 days and as an additional course for 2 days after the disappearance of symptoms. According to the results of examination and treatment of chlamydial pneumonia in children, combined treatment with antibacterial and antiviral drugs was accompanied by rapid positive dynamics; Symptoms of intoxication were relieved on the 3rd day, cough and shortness of breath stopped on average on the 5th day, percussion changes in the lungs normalized on the 6th day, X-ray dynamics - on the 8-9th day. Children tolerated the complex treatment well, no negative reactions were noted. Symptomatic therapy is carried out at the same time; Complex treatment with antibiotics and antiviral drugs has shown that they are most effective in reducing the severity of the disease. Thus, in the treatment of chlamydial pneumonia in children, the combined use of antibacterial and antiviral drugs is effective. The ease of use, availability of the drinkable form of the drug, high efficiency and absence of obvious side effects allow us to recommend this method of treatment for wide use in pediatrics and for the treatment of patients with inflammatory diseases of the respiratory tract.
Keywords: treatment; chlamydial pneumonia; children; complex treatment